Critical Theory and Constructivism in the Perspective of Islamic Epistemology - Noza Aflisia; Hendrianto Hendrianto; Nanat Fatah Nasir; Erni Haryanti (IAIN Palangka Raya, 2021)
This paper aims to analyze critical theory and constructivism as well as the Islamic perspective on these two things. This library research uses various references and references from existing books, national and international journals. The data obtained is then processed with data analysis techniques through the stages of collecting data on critical theory and constructivism through various sources and literature, understanding and analyzing the substance of critical theory and constructivism, and finding comparisons between the two, analyzing the Islamic perspective on critical theory and constructivism, and carry out verification and inference. The results show that critical theory invites us to realize that it is possible for a certain ideology to deliberately take advantage of the opportunity to make us neglect, then exploit, and take oppressive actions. While the constructivism paradigm presents an alternative in finding the truth about social reality, it also raises a shift in the rationality model in finding and establishing rules to a practical rationality model that emphasizes the role of examples and mental interpretation. In Islamic epistemology it is believed that humans not only know physical objects, but also non-physical objects. Muslim scientists use scientific methods that differ significantly from western scientists. Muslim scientists use the observation method (bayani) which comes from the senses, the logical or demonstrative method (burhani) which comes from the mind, and the intuitive method (irfani) which comes from the heart.Keywords: Critical Theory; Constructivism; Islamic Epistemology